Association between mode of anaesthesia and severe maternal morbidity during admission for scheduled Caesarean delivery: a nationwide population-based study in Japan, 2010–2013. (April 2018) - Abe, H.; Sumitani, M.; Uchida, K.; Ikeda, T.; Matsui, H.; Fushimi, K.; Yasunaga, H.; Yamada, Y.
Abstract: Background: Although the incidence of maternal mortality during Caesarean delivery remains very low, the rate of severe maternal morbidity is increasing. Improvements in obstetric anaesthetic practice have resulted in a dramatic reduction in the risk of maternal death from general anaesthesia. Less clear is whether the risk of severe maternal morbidity differs according to mode of anaesthesia for women undergoing Caesarean delivery. We analysed the association between the mode of anaesthesia and severe maternal morbidity during Caesarean delivery using a nationally representative inpatient database. Methods: We identified 89 225 women undergoing scheduled Caesarean delivery from the Diagnosis Procedure Combination database in Japan, 2010–2013. We defined severe maternal morbidity as the presence of any life-threatening complications and identified women with severe maternal morbidity from the database. Propensity score-matched analysis was carried out to compare the odds of severe maternal morbidity between women who underwent general vs neuraxial anaesthesia. Results: Of 89 225 women, 10 058 received general anaesthesia and 79 167 received neuraxial anaesthesia. In the propensity score-matched analysis with 10 046 pairs, a higher incidence of severe maternal morbidity was observed among patients receiving general (2.00%) rather than neuraxial anaesthesia (0.76%). The odds ratio of severe maternal morbidity was 2.68 (95% CI, 1.97–3.64) among women receiving general compared with neuraxial anaesthesia. Conclusions: For scheduled Caesarean delivery, general anaesthesia compared with neuraxial anaesthesia is associated with greater odds for severe maternal morbidity. However, we should be cautious with interpretation of these findings because they may be explained by confounding indications.